MUSHAF MENARA KUDUS CETAKAN 1974: Analisis Rasm dan Sumber Acuan Penulisan - Rif`atun Naajikhah (STAI AL-ANWAR SARANG, 2019)
Mushaf Pojok Menara Kudus is one of the most popular printed manuscripts for Indonesian publishers. This manuscript has its own uniqueness, namely from the writing model that does not use the Indonesian standard rasm (rasm Uthmāni). This research examines the history of writing the Mushaf Pojok Menara Kudus, the form of rhyme used and the characteristics of the Mushaf. The research is in library research, with primary data sources are interviews, kitab-kitab, books and other literature related to the Uthmāni rasm, rasm Imla'i and Mushaf Pojok Menara Kudus. This research concludes that Mushaf Pojok Menara Kudus is a copy of the Mushaf belonging to the caregiver of the Yanbu 'Al-Qurʻan Islamic Boarding School, KH. Arwani Amin, Mushaf Bahriyyah originating from Turkey. Every corner of the page always begins and ends with a verse and that's why this mushaf is called a corner mushaf. The rhymes used in the Mushaf Pojok Menara Kudus are mixed rasm, namely the Uthmāni rasm and the Imla'i rasm. The type of rhyme used then has several implications such as making it easier for reciter and memorizers, but it is troublesome for the common reader with the lack of instructions for Tajweed reading and the number of waqaf signs that have the same function.